2018
DOI: 10.33582/2639-4391/1006
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of fastrach LMA and ILMA methods for airway management

Abstract: The aim of this study is to compare the hemodynamic responses, durations of intubation, intubation success rates and postoperative upper airway complications between the intubation performed with direct laryngoscopy and blind intubation performed with LMA-Fastrach application in normotensive patients. This present study was performed with the approval of ethical committee and in the surgery rooms between the date March 2010-August 2010. The study was performed on 80 patients aged between 18 and 60 and had Amer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(27 reference statements)
1
1
0
Order By: Relevance
“…In several studies, intubation times were found to be significantly higher in LMA-Fastrach when compared to direct laryngoscopy in agreement with our study (Kihara et al, 2000;Sener et al, 2012;Kihara et al, 2001;Cırık et al, 2019). This is due to the fact that intubation using LMA-Fastrach involves 3 steps including insertion and confirmation of Fastrach position, insertion and confirmation of the endotracheal tube, and removal of the Fastrach.…”
Section: Discussionsupporting
confidence: 90%
“…In several studies, intubation times were found to be significantly higher in LMA-Fastrach when compared to direct laryngoscopy in agreement with our study (Kihara et al, 2000;Sener et al, 2012;Kihara et al, 2001;Cırık et al, 2019). This is due to the fact that intubation using LMA-Fastrach involves 3 steps including insertion and confirmation of Fastrach position, insertion and confirmation of the endotracheal tube, and removal of the Fastrach.…”
Section: Discussionsupporting
confidence: 90%
“…Laryngoscopy and endotracheal intubation (ETI) develop a sympathetic reflex response based on the mechanical stimulation of the larynx and trachea [ 6 ]. It is also known that ETI produces more postoperative pharyngolaryngeal morbidity, including voice change, compared to laryngeal masks [ 3 , 7 ].…”
Section: Introductionmentioning
confidence: 99%